Controlled Ovarian Hyperstimulation Protocol in Infertile Patients During the COVID-19 Pandemic - Li, Fei; Zhang, HuiXia; Shi, WeiYi; Wu, YiFang; Tian, Ye; Guo, YiHong; Jin, HaiXia; Li, Gang (Frontiers in Physiology, 2021)
Objectives: To explore the appropriate controlled ovarian hyperstimulation (COH) protocols in infertility patients who received the in vitro fertilization (IVF) / intracytoplasmic sperm injection (ICSI) treatments during the COVID-19 pandemic. Materials and Methods: This retrospective cohort study evaluated the efficiency of the early-follicular-phase long-acting GnRH-agonist long (EFLL) protocol (a new protocol developed by Chinese clinicians), prolonged pituitary down-regulation of EFLL protocol (Pro-EFLL) and the GnRH-ant protocol for couples meeting the study criteria between February 2020 and June 2020 who were treated by the First Affiliated Hospital of Zhengzhou University during the COVID-19 pandemic, and compared the pregnancy rates and miscarriage rates per fresh transfer cycle, number of retrieved oocytes, endometrial thickness on the day of hCG injection and the number of fertilized oocytes, mature oocytes, fertilized oocytes and transferable embryos among the three protocols. Results: We found that the prolonged pituitary down-regulation during the COVID-19 pandemic by utilizing a full-dose of GnRH-a administrated in infertility patients were no differences in clinical outcomes than other protocols, The prolonged pituitary down-regulation protocol and EFLL protocol were associated with a higher Endometrial thickness on the day of hCG injection (12.67±2.21 vs 12.09±2.35 vs 10.79±2.38, P < 0.001), retrieved oocytes (14.49±6.30 vs 15.02±7.93 vs 10.06±7.63, P < 0.001), mature oocytes (11.60±5.71 vs 11.96±6.00 vs 7.63±6.50, P < 0.001), fertilized oocytes (9.14±5.43 vs. 8.44±5.34 vs 5.42±5.20, P < 0.001) and transferable embryos (4.87±2.96 vs 6.47±5.12 vs 3.00±3.28 vs, P < 0.001) in the GnRH-antagonist protocol. Conclusions: We recommend that patients start Gn injections 33–42 days after a pituitary downregulated full dose (3.75 mg) of gonadotropin-releasing hormone agonist during the COVID-19 pandemic. The study can provide a more detailed estimate and clinical management strategies for infertile couples during the COVID-19 pandemic.